Experiences with curriculum development for aquaculture and fisheries educational institutions in Indochina and Northeast Thailand - Nielsen, Henrik Bechmann (AIT, 2003)
This volume serves a number of purposes. First, it documents more than sevent years of effort through the Danida-AIT project to develop aquaculture education and aquatic resources management in the three countries of Indochina and northeast Thailand.